2007
DOI: 10.1182/blood-2006-10-055327
|View full text |Cite
|
Sign up to set email alerts
|

NB1 mediates surface expression of the ANCA antigen proteinase 3 on human neutrophils

Abstract: Antineutrophil cytoplasmic antibodies (ANCAs) with specificity for proteinase 3 (PR3) are central to a form of ANCAassociated vasculitis. Membrane PR3 (mPR3) is expressed only on a subset of neutrophils. The aim of this study was to determine the mechanism of PR3 surface expression on human neutrophils. Neutrophils were isolated from patients and healthy controls, and hematopoietic stem cells from cord blood served as a model of neutrophil differentiation. Surface expression was analyzed by flow cytometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 42 publications
(46 reference statements)
10
108
0
2
Order By: Relevance
“…However, it is noteworthy that the membrane protein CD177, reported to be a protein that can associate with PR3 at the neutrophil plasma membrane, was not upregulated on apoptosis and was not part of this complex in RBL cells. Nonetheless, it was confirmed in this study that exogenous purified PR3 can specifically bind to CD177 expressed on resting RBL/CD177 cells, whereas no PR3 binding was observed on wild type RBL cells (data not shown), thus confirming earlier results (23,24) showing that CD177 is a receptor for exogenous PR3.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, it is noteworthy that the membrane protein CD177, reported to be a protein that can associate with PR3 at the neutrophil plasma membrane, was not upregulated on apoptosis and was not part of this complex in RBL cells. Nonetheless, it was confirmed in this study that exogenous purified PR3 can specifically bind to CD177 expressed on resting RBL/CD177 cells, whereas no PR3 binding was observed on wild type RBL cells (data not shown), thus confirming earlier results (23,24) showing that CD177 is a receptor for exogenous PR3.…”
Section: Discussionsupporting
confidence: 80%
“…In neutrophils, PR3 is expressed on the same neutrophil subset as CD177 (also called NB1) (23,24), a GPI-anchored glycoprotein. CD177 has been suggested to be a PR3 "receptor" involved in PR3 constitutive membrane expression in neutrophils, and we hypothesized that the lack of constitutive PR3 membrane expression of RBL/PR3 cells could be due to the absence of CD177 expression in these cells.…”
Section: Cd177 Is Not Associated With Membrane Pr3 On Apoptosismentioning
confidence: 99%
“…Molecular modeling and surface plasmon resonance demonstrated that PR3 can bind directly and robustly to the plasma membrane as well as lipid vesicles, and this binding occurs with a significantly higher affinity than HNE (27). Previously studies have shown that PR3 is expressed at the membrane of resting neutrophils through its ability to bind to CD177 (39,40). However, this type of interaction does not appear to play a role in apoptosis-induced membrane expression of PR3, which is independent of CD177 expression (11).…”
Section: Discussionmentioning
confidence: 95%
“…Although the vast majority of PR3 is stored intracellularly in primary granules together with other proteases, small amounts of PR3 prestored in as yet poorly characterized small vesicles are rapidly mobilized during priming. This small fraction of PR3 is externalized together with NB1 (CD177), a glycolipid-anchored membrane protein (5,6), and is presented on the neutrophil surface as a complex with NB1 (7). Simultaneous interaction of cANCAs with membrane-bound PR3 and FcgR is believed to trigger full activation and premature degranulation of extravasating neutrophils around small vessels in patients with active disease (3).…”
Section: W Egener's Granulomatosis (Wg) Is An Autoimmunementioning
confidence: 99%